AB1060 Are There Gender-Specific Differences in Patient Characteristics at Initiation of Biologic Treatment in Ankylosing Spondylitis and Psoriatic Arthritis?. (10th June 2014) - Bensen, W.G.; Kelsall, J.; Sheriff, M.; Jones, N.; Fortin, I.; Chow, A.; Shaikh, S.; Choquette, D.; Rampakakis, E.; Sampalis, J.S.; Nantel, F.; Shawi, M.; et al.
Abstract : Background: The prevalence of ankylosing spondylitis (AS) is 2-3 times higher in men compared to women whereas psoriatic arthritis (PsA) is generally considered a disease affecting both genders equally. Recent studies have suggested that clinical differences exist between men and women with the latter experiencing a higher burden of disease (1-4). Objectives: This analysis examined gender-specific differences with respect to patient and disease parameters at initiation of the first anti-TNF agent (infliximab; IFX) for the treatment of AS and PsA in a Canadian routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis (RA), ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with IFX or golimumab as first biologics or after having been treated with a biologic for <6 months. Patients with AS and PsA treated with IFX who were enrolled between 2005 and 2012 were included in this analysis. Results: Among the 303 AS patients and 91 PsA patients, 189 (62.4%) and 49 (53.3%) were male, respectively. Mean age and disease duration at initiation of IFX treatment were comparable between genders (Table 1 ). Overall, disease parameters in AS patients were similar between genders with the exception of CRP which was significantly lower in female patients and HAQ-DI which was significantly higher (Table 1 ). Among PsA patients, females reported a significantly greater functional disability and showed a higher DAS28 compared to men. Conclusions: Overall, some significant differences in disease parameters were observed between genders in AS and PsA at anti-TNF initiation. Female AS patients experience greater functional impairment compared to men. Female PsA patients, in addition to higher HAQ, also show greater disease activity as measured by DAS28. These results suggest that female patients appear to be receiving their first biologics at a higher level of disease activity. Whether this represents a gender bias in prescribing, or a gender based difference in the acceptance of biologic treatment, requires additional research. References: Lee W et al. Ann Rheum Dis. 2007 May;66(5):633-8. van der Horst-Bruinsma IE et al. Ann Rheum Dis. 2013 Jul;72(7):1221-4. Queiro R et al. Clin Dev Immunol. 2013;2013:482691. Eder L et al. Ann Rheum Dis. 2013 Apr;72(4):578-82. Disclosure of Interest: W. Bensen: None declared, J. Kelsall: None declared, M. Sheriff: None declared, N. Jones: None declared, I. Fortin: None declared, A. Chow: None declared, S. Shaikh: None declared, D. Choquette: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen Inc Canada, M. Shawi Employee of: Janssen Inc Canada, S. Otawa Employee of: Janssen Inc Canada, A. Lehman Employee of: Janssen Inc Canada DOI: 10.1136/annrheumdis-2014-eular.1911